Peranan Dana Zakat Produktif Terhadap Perkembangan Usaha Mikro Mustahik Pada Badan Amil Zakat Nasional Kabupaten Kutai Timur - Oktavianur, Arinda; Abdullah, Rais (Jurnal Ekonomi Syariah Mulawarman (JESM), 2022)
Arinda. Oktavianur. 2021. The Role of Productive Zakat Funds on the Development of Mustahik Micro Businesses in the National Zakat Agency of East Kutai Regency. Supervisor: Mr. Rais Abdullah.The purpose of this study is to determine whether there are differences in the condition of MSMEs before and after receiving the distribution of productive zakat funds from BAZNAS Kutim as seen from the indicators of sales turnover and business profits. The object of this research is the mustahik who as UMKM actors in Sangatta who get productive zakat funds from BAZNAS as many as 61 businesses. The type of data collected is primary data. The data analysis methods included descriptive statistics and the Wilcoxon sign rank test.The results showed: (1) that the rank test of the Wilcoxon sign on the sales turnover variable was a difference between the sales turnover before and after getting the distribution of productive zakat funds. (2) the Wilcoxon sign rank test on the Profit variable shows differences in business profits before and after obtaining distribution of productive zakat funds.